Influence of Different Types of Obstacles on the Propagation of Premixed Methane-Air Flames in a Half-Open Tube - Quan Wang (Energies, 2017)
To understand the propagation characteristics of methane-air deflagration flames and in an obstacle-filled tube, a high-speed color video camera, photoelectric sensors, and pressure transducers were used to test the deflagration flame propagating parameters. The tests were run in a 1500 mm long plexiglass tube with a 100 × 100 mm square cross-section. The obstacles included four types of repeated baffles and five forms of solid structure obstacles. The results showed that: (1) the flame front was constantly distorted, stretched, and deformed by different types of obstacles and, consequently, the flame propagating parameters increased; (2) plates and triple prisms increased the speed of the flame and overpressure to the highest extent, whereas cuboids and quadrangulars exerted an intermediate effect. However, the effect of cylindrical obstacles was comparatively limited. It was suggested that the obstacle’s surface edge mutation or curvature changes were the main factors stimulating the flame acceleration; (3) the peak pressure of deflagration was relatively low near the ignition end, increased gradually until it reached the maximum at the middle of the tube, and decreased rapidly near the open end; and (4) the fixed obstacles in front of the flame exhibited a blocking effect on flame propagation during the initial stages; the flame speed and overpressure increased when the flame came into contact with the obstacles. This study is of significance because it explains the methane-air propagation mechanism induced by different types of obstacles. The findings have value for preventing or controlling gas explosion disasters.